PENGARUH KOMPETENSI KERJA, DISIPLIN KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN DIVISI MARKETING DALAM MEMASARKAN PRODUK BUKU PELAJARAN PENERBIT DAN PERCETAKAN PT PRATAMA MITRA AKSARA - Ardiani Guswidjaya Krisnaningsih; Dyah Ayu Puri Palupi (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aims to identify and analyze the effects of job competence, work discipline, and incentives on employee performance. This study employs a quantitative method with a descriptive and associative approach. The population of this study consists of all 40 employees in the marketing division at PT Pratama Mitra Aksara. Data collection was conducted through the distribution of an online questionnaire, followed by data analysis using multiple linear regression to test the effect of each independent variable on the dependent variable. The results of the study indicate that job competence, work discipline, and incentives simultaneously have a positive and significant effect on employee performance. The t-scores for the Job Competence variable were 2.569, for the Work Discipline variable 2.894, and for the Incentives variable 2.998. Thus, it is concluded that improving job competence and work discipline, along with providing appropriate incentives, can enhance employee performance. It is hoped that this study will serve as a basis for companies to improve employee performance through more effective human resource management.